Gabapentin and Tricyclics in the Treatment of Post‐Concussive Headache, a Retrospective Cohort Study. Issue 3 (19th November 2018) - Cushman, Daniel M.; Borowski, Lauren; Hansen, Colby; Hendrick, John; Bushman, Troy; Teramoto, Masaru
Abstract : Objective: To examine the association of commonly prescribed post‐concussive medications, namely gabapentin and tricyclic antidepressants (TCAs), with symptom reduction after concussion. Background: Concussion is a common diagnosis in modern medicine. Many providers use medication to target the residual symptoms of a concussion, with little evidence supporting their efficacy. Design: Retrospective study with longitudinal analysis using mixed‐effects and piecewise regression analyses of 277 patients presenting to an academic sports medicine clinic, all of whom were clinically diagnosed with a concussion. Main outcomes were patient‐reported headache score (quantitative variable; 0–6) and combined symptom score (quantitative variable; 0–132) from the Post‐Concussion Symptom Scale (PCSS). Methods: Patients self‐reported their symptom scores on the PCSS at the time of each clinic visit. Gabapentin or TCAs were prescribed to some patients during their follow‐ups for headache treatment, based on physician judgment. Patients were classified into 3 groups: (1) no medication; (2) gabapentin; or (3) TCAs. Follow‐up data were evaluated over 1 year. A mixed‐effects and piecewise regression analysis were performed to assess long‐ and short‐term effects of medication status. Results: The mixed‐effects analysis showed a significant decrease in both headache and symptom scores over time in each medication group and in those not receiving medication ( P  ≤ .014 for all scenarios, B = −0.005 and −0.08, respectively). Although patients in the 2 medication groups showed significantly higher headache and symptom scores ( P  < .001), neither medication had a significant effect on longitudinal improvements in the outcome scores. The piecewise regression, however, showed short‐term improvements with gabapentin (1.3 points, P  = .004) and more sustained improvements with TCAs (3.5 points, P  = .006). Conclusions: Patients recover from a concussion with time, regardless of medication. Gabapentin and TCAs appear to have immediate effects on improving symptom burden, but long‐term outcomes show similar improvement compared to those who are not prescribed medication. More rigorous prospective studies are required to better elucidate their efficacy.